Epidemiology and clinical profile of vitiligo in Ibadan, Nigeria - Anaba, Ehiaghe L.; George, Adekunle O.; Ogunbiyi, Adebola O. (International Journal of Research in Medical Sciences, 2018)
Background: Vitiligo patients are seen routinely in the Dermatology Outpatient Clinic of the University College Hospital Ibadan, Nigeria. However, the epidemiologic and clinical profile of these patients is not documented. The aim of this study was to document the clinical (age of onset, location, severity, class of vitiligo) and sociodemographic characteristics of these patients. Methods: This is a retrospective descriptive study of patients treated for vitiligo from January 2005 to December 2009 at the University College Hospital (UCH) Ibadan dermatology outpatient clinic. Patient records were retrieved and a study proforma was used to assess patient’s information. Data was analyzed using SPSS version 16. Results: Over the study period, 130 vitiligo patients seen but only 111 case notes were retrieved. The mean age at onset in children was 7.8±4.0 and 34.6±17.1 in adults, M:F was 1:1. The commonest type of vitiligo was acrofacial, area of onset was the face/scalp in 59.2%, re-pigmentation was reported in 66%, active lesions in 59.7%, severity of vitiligo was <9% in 90%, Vitiligo was in visible (exposed) parts of the body 84.7% and asymptomatic in 92.7%. Conclusions: The clinical profile of vitiligo in Ibadan, Nigeria is similar to that observed in other places with only females having a genital onset and acrofacial vitiligo being the dominant type seen. Also, treatment modality varies between children and adults.